Diet Quality and Depression in A Midlife Biracial Cohort of Women: The Role of Stress And Early Life Adversity. (29th May 2020) - Chiu, Dorothy; Leung, Cindy; Epel, Elissa; Laraia, Barbara
Abstract: Objectives: Stress exposure may impose an altered physiological state to modify relations between diet and the brain. We investigate if current perceived stress and childhood trauma might moderate diet quality and depression risk associations in women. Methods: Preliminary data for white and black women ( n  = 326, mean age: 39 y) taking part in the National Growth and Health Study follow-up were analyzed by multiple logistic regression models. Women at-risk for depression (score ≥ 16) were identified by the CES-D scale. Alternative Healthy Eating Index (AHEI)-2010 scores (continuous) were calculated from 3-day food records (averaged). Current perceived stress (scoring in the top tertile on Cohen's Perceived Stress Scale; here ≥20) and past childhood trauma (any exposure to physical abuse, sexual abuse, or a household member afflicted with addiction) were examined as effect modifiers (binary). Interaction terms between AHEI scores and each stress measure were tested in crude and final logistic models adjusted for race, income, and health status. Subsequent marginal analyses evaluated significance of differences in predicted probability of depression risk between stressed and non-stressed groups over AHEI. Results: Interactions between AHEI and high perceived stress ( P  = 0.03), past physical abuse ( P  = 0.08), and past sexual abuse ( P  = 0.04) were significant in crude models. After adjustment, AHEI with high stress ( P  = 0.04) and physical abuse ( P  = 0.09) maintained some significance. In crude and adjusted models, predicted probabilities of depression risk were significantly higher ( P  < 0.05) in high vs. low perceived stress women, as well as between women with past physical or sexual abuse vs. those without. However, these differences were only observed for AHEI scores above certain thresholds (in adjusted analyses: approx. AHEI ≥35 for high perceived stress, AHEI ≥58 for physical abuse, and AHEI ≥55 for sexual abuse). For AHEI scores outside those ranges, differences between predicted probabilities of depression were not seen ( P > 0.05). Prior living with addiction did not modify diet-depression relations ( P > 0.05). Conclusions: Complex interplay between stress and adversity, diet quality, and depression in adult women exists, substantiating need for more research to understand underlying vulnerabilities and potential dietary intervention. Funding Sources: NIH/NICHHD.